MAKNA FILOSOFIS ELEMEN ELEMEN PERTUNJUKAN WAYANG KULIT LEMAH BALI - I Putu Ardiyasa (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Wayang kulit art has many types, one of which is the Weak Wayang as a sacred performance that is used as an accompaniment to a yadnya ceremony. As the name suggests Weak puppets should be performed during the day and in line with the accompanying yad, but if the ceremony takes place at night, still use the Weak Puppet Show, because its main function is to accompany the Panca yadnya, namely: Manusa Yadnya, Pitra Yadnya, Dewa Yadnya, Bhuta yadnya and yadnya receipt. This research seeks to examine in more depth the elements of the Weak Skin Puppet show from a philosophical aspect. The research data was obtained through observation, interviews with five masterminds and looked for additional data through literature study. this research shows that each of the elements (people, puppets, gamelan and supporting properties) have interconnected philosophical meanings.